1999
DOI: 10.1083/jcb.145.2.291
|View full text |Cite
|
Sign up to set email alerts
|

Mgm101p Is a Novel Component of the Mitochondrial Nucleoid That Binds DNA and Is Required for the Repair of Oxidatively Damaged Mitochondrial DNA

Abstract: Maintenance of mitochondrial DNA (mtDNA) during cell division is required for progeny to be respiratory competent. Maintenance involves the replication, repair, assembly, segregation, and partitioning of the mitochondrial nucleoid. MGM101 has been identified as a gene essential for mtDNA maintenance in S. cerevisiae, but its role is unknown. Using liquid chromatography coupled with tandem mass spectrometry, we identified Mgm101p as a component of highly enriched nucleoids, suggesting that it plays a nucleoid-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
84
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 53 publications
4
84
0
1
Order By: Relevance
“…Together with the hypersensitivity of the mgm101 N150A mutant to hydrogen peroxide and other DNAdamaging agents (26), the data strongly support a role of the protein in recombinational repair in vivo. Recombination between non-tandem direct repeats generally results from recombinational repair of dsDNA breaks, which are mediated either by non-allelic strand invasion between the repeats or by annealing of non-allelic repeated sequences after exonuclease resection of dsDNA breaks.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Together with the hypersensitivity of the mgm101 N150A mutant to hydrogen peroxide and other DNAdamaging agents (26), the data strongly support a role of the protein in recombinational repair in vivo. Recombination between non-tandem direct repeats generally results from recombinational repair of dsDNA breaks, which are mediated either by non-allelic strand invasion between the repeats or by annealing of non-allelic repeated sequences after exonuclease resection of dsDNA breaks.…”
Section: Discussionmentioning
confidence: 57%
“…Mature Mgm101 is a positively charged protein of 247 amino acids (25). Nunnari and co-workers (26,27) have shown that Mgm101 is associated with actively replicating mitochondrial nucleoids and that mtDNA in mgm101 mutants is hypersensitive to several DNA-damaging agents, including ultraviolet, ␥-ray irradiation, and hydrogen peroxide. These observations strongly suggested a role for Mgm101 in mtDNA repair.…”
mentioning
confidence: 99%
“…A number of mt (cp) nucleoid proteins have been identified in yeast (39)(40)(41)(42), algae (43), and plants (44,45). An intriguing example of a mt nucleoid protein is Glom, which is a structural nucleoid protein that also maintains the replication and transcriptional activity of mtDNA in slime mold (46).…”
Section: Discussionmentioning
confidence: 99%
“…By this method, roughly 20 polypeptide species are enriched, but only a few of them have been identified. Known nucleoid proteins include Abf2p, an abundant, high-mobility group protein required for the stability of wild-type ( ϩ ) mtDNA in cells grown on fermentable carbon sources (4), as well as for efficient mtDNA recombination (5,6), and Mgm101p, a protein possibly involved in mtDNA repair that is also required for the stability of ϩ mtDNA (7,8). Cells lacking Abf2p can maintain ϩ mtDNA when grown on nonfermentable carbon sources, and based on morphological and biochemical criteria, the mtDNA is organized differently than in wild-type cells (2,5).…”
mentioning
confidence: 99%